SUBSTAMINALE DEVELOPMENT IN AGRICULTURAL INVESTMENTS AND THE FOOD SECURITY SYSTEM - Gelena Pruntseva, Bohdan Danylyshyn, Nazariy Popadynets, Oksana Kopylyuk, Igor Kotsan (EDP Sciences, 2024)
Agricultural investments play a crucial role in boosting productivity, reducing poverty, and enhancing food security. By increasing food availability and stabilizing prices, these investments make essential food more accessible to low-income groups. They also foster rural development through job creation and infrastructure growth, contributing to poverty reduction and consistent food consumption. In the face of challenges like climate change, shrinking land availability, declining fertility, and water scarcity, agricultural investments are vital for sustaining and increasing production. As global population growth heightens food demand, effective investment becomes even more critical to prevent famine. However, expanding agricultural land is limited, so future agricultural growth will rely on productivity improvements driven by investments. It is imperative for governments to create a conducive environment to attract such investments while ensuring that they are allocated efficiently. Mismanagement or ineffective use of investments can lead to negative social and environmental impacts. Therefore, continuous monitoring and analysis of agricultural investments are essential to maximize their effectiveness in ensuring food security.
Physical & Chemical Geotechnologies 2024. Pp.1-10.